PENGEMBANGAN KULIAH DARING TERBUKA MASSAL (KDTM) MATA KULIAH OLAHRAGA TRADISIONAL UNTUK MAHASISWA PROGRAM STUDI OLAHRAGA REKREASI - Ali, Masnur (Dharmas Journal of Sport, 2025)
Traditional sports are sports that have been passed down from generation to generation and inherited by ancestors which are characteristics that cannot be separated from the culture and customs of a region. This study aims to produce a Mass Open Online Lecture Learning for traditional sports courses. The development of this Mass Open Online Lecture Learning for traditional sports will be used for recreational sports study program students who take traditional sports courses according to the learning outcomes of traditional sports, namely playing traditional games and preserving traditional sports by playing games that can improve motor skills, shape children's character attitudes and types of traditional sports that have been standardized. The research location was conducted at the Laboratorium Olahraga Masyarakat FIKK UNJ. The subjects in this study were 50 third semester recreational sports study program students. Data collection techniques were conducted by conducting observations related to the needs in developing KDTM, research interviews, documentation and validating products. This research is a development research or Research & Development with the SAM approach. By using SAM, the development process becomes faster, more responsive, and more adaptive to the needs of students. The research results produced a mass open online lecture learning tool that is 90% practical for use in the learning process.